2021
DOI: 10.3390/su13042069
|View full text |Cite
|
Sign up to set email alerts
|

(Un)Sustainability of the Time Devoted to Selected Housework—Evidence from Slovakia

Abstract: Domestic appliances play a vital role in modern households. Appliances help simplify domestic work, but individuals become dependent on them. The present paper aims to contribute to the long-standing dilemma among scholars whether domestic appliances help to shorten the time devoted to household chores or not. The paper focuses on the utilization of various domestic appliances in Slovak households and on the influence of their utilization on the time of men and women in partner households and in the single-per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 79 publications
0
2
0
Order By: Relevance
“…Therefore, boosting economic development is a priority for social sustainable development. In addition, not only in some of the literature [1, [63][64][65][66], but also in our own work, we have found that regulating social policies to transform gender norms-such as improving women's political participation status, promoting women to enter the core position of society, and correcting the traditional gender norms through concept education, training, propaganda etc.-plays a positive role in gender equality, and benefits the development of social sustainability. Moreover, these research results further indicate that promoting economic development, the governance of the sex ratio imbalance, the improvement of government-provided childcare services, and setting up the elderly care system could also create favorable conditions for gender equality and sustainable social development.…”
Section: Discussionmentioning
confidence: 52%
“…Therefore, boosting economic development is a priority for social sustainable development. In addition, not only in some of the literature [1, [63][64][65][66], but also in our own work, we have found that regulating social policies to transform gender norms-such as improving women's political participation status, promoting women to enter the core position of society, and correcting the traditional gender norms through concept education, training, propaganda etc.-plays a positive role in gender equality, and benefits the development of social sustainability. Moreover, these research results further indicate that promoting economic development, the governance of the sex ratio imbalance, the improvement of government-provided childcare services, and setting up the elderly care system could also create favorable conditions for gender equality and sustainable social development.…”
Section: Discussionmentioning
confidence: 52%
“…Social norms play a significant role in the burden of housework and women's employment, particularly for married women or women with partners. Studies do not show that household improvement reduces the housework time for women (Bittman et al, 2004;Knapková & Považanová, 2021;Vu, 2019). These studies were followed by the bargaining power model, where individuals are egoistic and have different utility functions (Chiappori, 1988).…”
Section: Literature Reviewmentioning
confidence: 99%